Pepper Powder Quality Identification System Based on Silent Angle Imagery - Muhaimin Gusrin; Abdul Fadlil (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
This research identifies the quality of pepper powder using a computer automatically. The research method uses the stationary angle method. The design of this system is done by image processing techniques. The image of ground pepper that has been taken is then cropped to remove the unused portion of the image. The next step is to convert the original image into grayscale and then convert it to binary. The parameter of the stationary angle is when it has an angle of less than or equal to 38 Â°, the ground pepper includes fine ground pepper. If the angle ranges from 38o to 40o, including medium powdered pepper, and if the angle is greater than 41o, including the texture of coarse pepper powder. Testing 3 different types of samples obtained 40 mesh is 35.18 o; for 20 mesh is 40.46o and 10 mesh is 41.66o. Therefore, it can be seen that the smaller the texture of the size of ground pepper, the finer the quality.Penelitian ini mengidentifikasi kualitas lada bubuk menggunakan komputer secara otomatis. Metode penelitian menggunakan metode sudut diam. Perancangan sistem ini dilakukan dengan teknik pengolahan citra. Citra lada bubuk yang telah diambil selanjutnya di-cropping untuk menghilangkan bagian citra yang tidak terpakai. Langkah selanjutnya adalah citra hasil asli tersebut dikonversi dalam bentuk grayscale dan selanjutnya dikonversi dalam bentuk biner. Parameter sudut diam adalah ketika memiliki sudut kurang dari atau sama dengan 38o, lada bubuk tersebut termasuk lada bubuk yang halus. Jika sudutnya berkisar antara 38o sampai 40o maka termasuk lada bubuk sedang, dan jika sudutnya lebih besar dari 41o maka termasuk tekstur lada bubuk kasar. Pengujian 3 jenis sampel yang berbeda didapatkan 40 mesh adalah 35,18o; untuk 20 mesh adalah 40,46o dan 10 mesh adalah 41,66o. Oleh karena itu dapat diketahui bahwa semakin kecil tekstur ukuran lada bubuk, semakin halus kualitasnya.